A Three Component Self‐Assembled Epitaxial Nanocomposite Thin Film. (10th April 2015) - Kim, Dong Hun; Sun, Xue Yin; Aimon, Nicolas M.; Kim, Jae Jin; Campion, Michael J.; Tuller, Harry L.; Kornblum, Lior; Walker, Fred J.; Ahn, Charles H.; Ross, Caroline A.
Abstract : A self‐assembled three phase epitaxial nanocomposite film is grown consisting of ≈3 nm diameter fcc metallic Cu nanorods within square prismatic SrO rocksalt nanopillars in a Sr(Ti, Cu)O3‐ δ perovskite matrix. Each phase has an epitaxial relation to the others. The core–shell‐matrix structures are grown on SrTiO3 substrates and can also be integrated onto Si using a thin SrTiO3 buffer. The structure is made by pulsed laser deposition in vacuum from a SrTi0.75 Cu0.25 O3 target, and formed as a result of the limited solubility of Cu in the perovskite matrix. Wet etching removes the 3 nm diameter Cu nanowires leaving porous SrO pillars. The three‐phase nanocomposite film is used as a substrate for growing a second epitaxial nanocomposite consisting of CoFe2 O4 spinel pillars in a BiFeO3 perovskite matrix, producing dramatic effects on the structure and magnetic properties of the CoFe2 O4 . This three‐phase vertical nanocomposite provides a complement to the well‐known two‐phase nanocomposites, and may offer a combination of properties of three different materials as well as additional avenues for strain‐mediated coupling within a single film. Abstract : nc‐STCu films are grown in vacuum on Nb‐doped (001) STO substrate after etching in ammonium hydroxide for 3 h. Metallic copper rods with ≈3 nm diameter grow in the center of the SrO nanorods in a perovskite matrix, and etching of the Cu by ammonium hydroxide creates uniformly sized nanopores.